Extracorporeal Membrane Oxygenation in Postcardiotomy Pediatric Patients—15 Years of Experience Outside Europe and North America - ElMahrouk, Ahmed F.; Ismail, Mohamed Fouad; Hamouda, Tamer; Shaikh, Rafik; Mahmoud, Alaa; Shihata, Mohammad Sabry; Alradi, Osman; Jamjoom, Ahmed (The Thoracic and Cardiovascular Surgeon, 2019)
Background The increasing complexity of congenital cardiac surgery has resulted in the increased use of extracorporeal membrane oxygenation (ECMO) support for children who cannot be weaned from cardiopulmonary bypass. The purpose of this research was to assess the mortality and morbidity in children requiring ECMO support after the repair of congenital heart defects (CHDs).Methods The hospital records of all patients with CHD who required ECMO after a cardiac surgical procedure between January 2001 and December 2016 were retrospectively reviewed. Various outcomes were reported and tested for any association with hospital death.Results A total of 113 children required ECMO for cardiopulmonary support after congenital cardiac surgery; 88 (77.9%) were placed on ECMO in the operating room. Median age of the patients was 3 months (range, 4 days–15 years) and median weight was 3.5 kg (range, 2.2–42.5). Forty-two (37.2%) survived to hospital discharge. In children with single-ventricle physiology, survival to discharge was 37.3% (19/51 patients) and for biventricular physiology, it was 37.1% (23/62 patients). Univariate analysis revealed number of days on ECMO support, renal failure, and stroke as risk factors for hospital mortality, while age and cross-clamp time were found to be statistically nonsignificant.Conclusion Satisfactory results can be achieved in pediatric patients by using ECMO support for postoperative cardiac and pulmonary failure refractory to medical management. Prolonged ECMO support, renal failure, and stroke are risk of mortality.
Keywords: extracorporeal membrane oxygenation; congenital heart disease; pediatric; cardiac surgery